2012
DOI: 10.1371/journal.pone.0035595
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Dependent Association of EBP50 with Protein Phosphatase 2A in Endothelial Cells

Abstract: Ezrin-radixin-moesin (ERM)-binding phosphoprotein 50 (EBP50) is a phosphorylatable PDZ domain-containing adaptor protein that is abundantly expressed in epithelium but was not yet studied in the endothelium. We report unusual nuclear localization of EBP50 in bovine pulmonary artery endothelial cells (BPAEC). Immunofluorescent staining and cellular fractionation demonstrated that EBP50 is present in the nuclear and perinuclear region in interphase cells. In the prophase of mitosis EBP50 redistributes to the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…The PP2A phosphatase complex binds and dephosphorylates NHERF1 (Boratkó et al, 2012; Chen et al, 2012). We examined the localization of the NHERF1-associating PP2A-B55α subunit (3×HA-PP2A-Bα).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PP2A phosphatase complex binds and dephosphorylates NHERF1 (Boratkó et al, 2012; Chen et al, 2012). We examined the localization of the NHERF1-associating PP2A-B55α subunit (3×HA-PP2A-Bα).…”
Section: Resultsmentioning
confidence: 99%
“…Internalized Podxl transcytoses to the AMIS (Bryant et al, 2010), likely now in association with NHERF2 (Figure 7G, box 4). The Podxl- NHERF1-Ezrin complex reforms at the AMIS via corecruitment of phosphatase PP2A (Figure 7G, box 5), probably promoting dephosphorylation of Podxl-NHERF1 (Boratkó et al, 2012; Chen et al, 2012). The AMIS then progresses to an open lumen, surrounded by a monolayer of AP-BL polarized epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, many studies have focused on EBP50, which is widely distributed and is particularly rich in tissues with polarized epithelia with numerous ezrin-radirin-moesin (ERM) family members, such as the liver, kidney, small intestine and placenta [20]. In addition to acting as a scaffold protein linking transmembrane proteins to various cytoskeletal proteins, EBP50 is localized in the plasma membrane and the cytoplasm of epithelial cells [21]. Hence, it can be deduced that EBP50 may be expressed in the apical plasma membrane of polarized epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…During decidualization, uterine stroma cells start to proliferate and differentiate into decidual cells, which also undergo extensive remodeling to control embryo invasion and accommodate the growing embryo. Boratko et al [21] had reported that EBP50 is present in the nuclear and perinuclear regions in interphase cells. However, EBP50 redistributes to the cytoplasmic region during the prophase of mitosis.…”
Section: Resultsmentioning
confidence: 99%
“…When EBP50 is phosphorylated by either Cdc2 (cell division cycle 2) or PKC, it is unable to bind to PDZ1 and PDZ2 ligands simultaneously and is unable to form microvilli perhaps due to unidentified PDZ2 ligand(s) which preferentially bind to its phosphorylated form [53]. The phosphoregulation of EBP50 activity is also involved in regulating EBP50’s localization and activity in endothelial cells and other epithelial cell lines [57, 58]. …”
Section: Ebp50 and Microvillimentioning
confidence: 99%